2013
DOI: 10.1007/s11999-013-3243-9
|View full text |Cite
|
Sign up to set email alerts
|

Death, Taxes, and Trapeziometacarpal Arthrosis

Abstract: Background Hand surgeons treat trapeziometacarpal arthrosis as if everyone with the disease presents for treatment despite evidence that suggests that trapeziometacarpal arthrosis is a normal part of human aging for which-it seems safe to assume-most people never seek medical attention. Questions/purposes The aims of our study were (1) to confirm the prevalence of radiographic trapeziometacarpal arthrosis in a very large sample and to determine if age and sex are associated with (2) any radiographic evidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 7 publications
3
79
1
1
Order By: Relevance
“…Female sex and older age are associated with greater pathophysiology [3,19], but patients who saw additional providers and who were younger were associated with greater costs and greater likelihood of surgery; the latter also increased in male patients. With our large cohort of patients, those with less severe disease used more extensive medical services.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Female sex and older age are associated with greater pathophysiology [3,19], but patients who saw additional providers and who were younger were associated with greater costs and greater likelihood of surgery; the latter also increased in male patients. With our large cohort of patients, those with less severe disease used more extensive medical services.…”
Section: Discussionmentioning
confidence: 98%
“…Another study found that women are more willing to delay surgery to await better technology and avoid disrupting of their caregiver roles [12]. The high prevalence of hand OA that occurs with increasing age suggests that most people adapt to it [3,5]. Delaying surgery, something that may come more naturally to women might prevent surgery altogether.…”
Section: Discussionmentioning
confidence: 99%
“…High compressive forces through the CMC joint, up to 120 kg with power grasp and 12 kg with tip pinch [8], may predispose this joint to degenerative arthritis. Arthritis of this joint more commonly occurs in women than in men, starting in middle adulthood and increasing in prevalence with age [14]; radiographic prevalence ranging from 33% of postmenopausal women [1] to as high as 100% of women older than 91 years is described [4]. The anterior oblique ligament incompetence has been shown to play a role in the progression of CMC arthritis [3,7,19,20].…”
Section: Historymentioning
confidence: 99%
“…Although Eaton and Littler described their radiographic classification to be used to guide surgical intervention [12], the radiographic presence of basilar thumb arthritis is nearly inevitable with age [4], and surgery should be considered only if extensive nonsurgical treatment options have been exhausted and lifestyle limiting pain and disability persists.…”
Section: Purposementioning
confidence: 99%
“…In fact, the symposium explored a broad range of clinical and laboratory research, and some very interesting history on the topic [4]. When we combine this excellent symposium with the epidemiology research that extended our understanding of this joint to the final decades of life [1], and place them alongside this award-winning study, it becomes clear that this has been a very good year at CORR 1 in terms of what we have learned about this complex joint.…”
mentioning
confidence: 99%